Income-related inequality in Body Mass Index: The effects of the 2008 economic collapse in Iceland - Nína Þrastardóttir 1985- (2013)
Background and aims: How mortality and morbidity measures are related to business cycles has gotten increased attention with the great economic recession. Similarly income-related health inequality has been studied in many countries and in recent years more researches have measured income-related health inequality with concentration index and concentration curve. However the relationship between macroeconomic conditions and income-related health distribution has received limited attention. What happens when an economy collapses? Recent results have indicated that physical health can actually improve in recession. Data and methods: The data used in this thesis is longitudinal and originated from a health and lifestyle survey carried out by The Public Health Institute in 2007 and again in 2009. The goal of this survey was to gather information about health, wellbeing, quality of life and diseases of people in Iceland using a stratified random sampling method. To evaluate income-related health inequality concentration indexes were computed and concentration curves graphed. The variables used to measure living standards were individual income and equivalent household income, both before taxes. The variable used to measure health status was Body Mass Index. Results: Income-related health inequality is not to be detected in Iceland in 2007 or 2009 when considering equivalent household income. The concentration curves almost coincide with the line of equality. The concentration indexes are almost the same between the years and very close to zero indicating no difference between the years. When considering individual income, there is also little or no income-related health inequality to be detected in 2007 or in 2009 when looking at the whole sample. Actually the concentration curve in 2009 goes a little bit closer to the line of equality meaning less income-related inequality one year after the economic collapse and the concentration index swifts from being positive to negative. The only evidence of income-related ...